Disruption of Neutrophil Extracellular Traps (NETs) Links Mechanical Strain to Post-traumatic Inflammation - Agarwal, Shailesh; Loder, Shawn J.; Cholok, David; Li, John; Bian, Guowu; Yalavarthi, Srilakshmi; Li, Shuli; Carson, William F.; Hwang, Charles; Marini, Simone; Pagani, Chase; Edwards, Nicole; et al. (Frontiers in Immunology, 2019)
Inflammation after trauma is both critical to normal wound healing and may be highly detrimental when prolonged or unchecked with the potential to impair physiologic healing and promote de novo pathology. Mechanical strain after trauma is associated with impaired wound healing and increased inflammation. The exact mechanisms behind this are not fully elucidated. Neutrophil extracellular traps (NETs), a component of the neutrophil response to trauma, are implicated in a range of pro-inflammatory conditions. In the current study, we evaluated their role in linking movement and inflammation. We found that a link exists between the disruption and amplification of NETs which harbors the potential to regulate the wound's response to mechanical strain, while leaving the initial inflammatory signal necessary for physiologic wound healing intact.